Bahasa Inggris - Maulana, Lukman Akbar; Ahmad, Yousef Bani; Kartini, Dedeh (Peneliti.net, 2024)
This qualitative study explored pre-service English teachers’ behavioral, normative, and control beliefs toward their intentions to including explicit pronunciation instruction in their future classrooms. The theoretical framework was based on the Theory of Planned Behavior (TPB) by (Ajzen, 1991) In order to understand these beliefs and the intentions of pre-service English teachers for providing pronunciation instruction. According to Ajzen’s TPB, the behavioral beliefs are based on attitude regarding the benefit or consequences of applying pronunciation instruction, the normative beliefs stand on social support and pressure to apply pronunciation instruction, and the control beliefs lay the foundation of perceived behavioral control over applying pronunciation instruction in a classroom. Data were collected from open-ended survey questions (n=30), semi-structured interviews (n=8) and end of semester reflections (n=8). The findings suggests that pre-service English teachers’ intentions to apply pronunciation instruction are related to their beliefs about the value of these instruction for improving student speech intelligibility, enhance quality of learning engagement and finding wider opportunity in the future (behavioral beliefs), its ability to meet the student needs and wants (normative beliefs), the participants’ high self-efficacy in pronunciation, and its potential for providing interactive classroom activities (control beliefs). From these results, we recommend that teacher educators should target these beliefs within teacher development programs to prepare pre-service English teachers for successful apply of pronunciation instruction in their future classrooms.